2013
DOI: 10.1007/s12272-013-0236-x
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic compounds with IL-6 inhibitory activity from Aster yomena

Abstract: A new biflavonoid, named asteryomenin (1), as well as six known phenolic compounds, esculetin (2), 4-O-β-D-glucopyranoside-3-hydroxy methyl benzoate (3), caffeic acid (4), isoquercitrin (5), isorhamnetin-3-O-glucoside (6), and apigenin (7) were isolated from the aerial parts of Aster yomena. The structures of compounds (1-7) were identified based on 1D and 2D NMR, including (1)H-(1)H COSY, HSQC, HMBC and NOESY spectroscopic analyses. Compounds 2-7 were isolated from this plant for the first time. For these iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 17 publications
1
26
0
Order By: Relevance
“…Isoquercitrin is a well-known antioxidant [31] with free radical scavenging activity [32]. It shows antiallergic [33] and anti-inflammatory effects in vitro [34,35] as well as in vivo [36]. In this current study, we analyzed the whole decoction and demonstrated a significant inhibitory influence on the inflammatory process of human immunocompetent cells.…”
Section: Discussionmentioning
confidence: 71%
“…Isoquercitrin is a well-known antioxidant [31] with free radical scavenging activity [32]. It shows antiallergic [33] and anti-inflammatory effects in vitro [34,35] as well as in vivo [36]. In this current study, we analyzed the whole decoction and demonstrated a significant inhibitory influence on the inflammatory process of human immunocompetent cells.…”
Section: Discussionmentioning
confidence: 71%
“…Subfraction D113 (900.9 mg) was subjected to silica gel CC using a gradient solvent system of chloroform:MeOH (30:1 → 100% MeOH). Of the six subfractions that were collected (D1131-D1136), subfraction D1135 (113.2 mg) was purified by semipreparative high-performance liquid chromatography (75% MeOH), resulting in the isolation of compound 1 (apigenin, 3.9 mg) [9]. Apigenin was dissolved in dimethyl sulfoxide to reach a final concentration of 10 mg/ml.…”
Section: Reagentmentioning
confidence: 99%
“…Aster yomena is a perennial herb that is found mainly in South Korea [9]. In traditional Korean Buddhism, A. yomena is included in a mix of vegetables and spices that are valued for their medical effects [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…It is extracted and its chemical structure was identified according to Kim et al's method (Supporting Information Fig. S1) (8). A stock solution of ISO was dissolved in dimethyl sulfoxide (DMSO) and stored at −20 C. In all experiments, DMSO was used at <5% of the total volume (18).…”
Section: Preparation Of Iso and Antifungal Agentsmentioning
confidence: 99%